Lipid bilayer modification induced by fibrillar lysozyme: fluorescence spectroscopy study - Kastorna, A.P.; Trusova, V.M.; Gorbenko, G.P. (Харьковский Национальный Университет им. В.Н.Каразина, 2010)
The correlation between neurodegenerative diseases (Parkinson’s, Alzheimer’s diseases), type II diabetes, systemic amyloidosis, etc. and deposition of protein aggregates in brain and other tissues has long been established. A growing body of evidence has demonstrated that binding of amyloid proteins to the membrane may underlie their cytotoxic effect. It was shown that amyloid toxicity arises primarily from a soluble oligomeric form (pre-fibrillar aggregates) of the peptide rather than amyloid monomers or mature fibrils. The molecular basis of the amyloid protein toxicity is not sufficiently clear and requires further investigation. In view of this, the present study has been undertaken to ascertain the effect of fibrillar aggregates of lysozyme on the structural and physical properties of model membranes (liposomes) composed of zwitterionic lipid phosphatidylcholine and its mixture with cholesterol (30 mol%). To this end, two fluorescent probes with different properties and bilayer location, pyrene and Laurdan, have been employed. Pyrene spectra have characteristic vibronic structure in the region of 370-400 nm. Relative intensities of vibronic transitions exhibit dependence on solvent polarity. Excited species of pyrene can interact with non-excited ones thus forming excited state dimers – excimers. Excimer-to-monomer fluorescence intensity ratio reflects the extent of pyrene excimerization, which depends mainly on the rate of monomer lateral diffusion in lipid bilayer, being a function of the density of lipid molecular packing. Analysis of pyrene emission spectra revealed the absence of any influence of fibrillar lysozyme on the structural state of bilayer acyl chain region. Laurdan is an amphiphilic fluorescent probe, whose emission spectra are sensitive to the environmental polarity (hydration level). In the solvents of high polarity, Laurdan shows a considerable shift of its emission spectrum to longer wavelengths due to the dipolar relaxation processes. The changes in the emission spectrum of Laurdan were characterized by the generalized polarization value (GP). In all types of liposomes increasing concentration of fibrillar lysozyme resulted in the increment of GP, suggesting that amyloid fibrils cause the decrease in the lipid bilayer polarity.
Keywords: amyloid; lysozyme fibrils; pyrene; Laurdan; model membranes